The Creation of the Community of Political Prisoners and Resistance in the GULAG Special Regime Camps (1948–1954) - Gelumbauskas, Evaldas (Genocidas ir rezistencija, 2004)
This article analyses the evolution of the system of GULAG special regime camps during 1948–1954 and the development of the status, identity and the formation of the community of political prisoners incarcerated there, as well as the resistance and struggle of political prisoners for the liquidation of the special imprisonment regime in the camp is also reviewed. The author of the article summarizes the most recent works of Lithuanian and foreign historians, and has utilized an abundance of memoirs of former political prisoners and sources published in separate collections of documents.The Soviet Union officially maintained that there were no political prisoners in the country, only persons who had committed crimes against the state. Articles on anti-state crimes of the criminal codes of Soviet republics were applied broadly in practice. Their wording meant that not only ideological enemies of the Soviet state and the system were covered by the political charges, but also affected apolitical Soviet citizens. Therefore, political prisoners imprisoned in the GULAG for anti-state crimes for a long time failed to form an ideologically uniform and purposeful community able to successfully resist abuse at the hands of the camp administration and criminal prisoners.However, after the Second World War the composition of the political prisoner population changed: more determined and active enemies of the Soviet system were imprisoned in camps, including members of anti-Soviet armed resistance and underground youth organisations. This not only changed the situation of political prisoners in the camps, but also was one on the main reasons for separating political prisoners from the general prisoner population in 1948 and moving the politicals to camps of special regime.Camps of special prison regimes, which were active in 1948–1954, possessed features of both camps and closed prisons. Their aim was to isolate and then physically and morally break the most active enemies of the Soviet state. However, despite the strict regime, special camps became the main place for the political prisoners' consciousness-raising and discovery of their identity. Continuing their tradition of armed resistance, members of resistance movements who were imprisoned in camps after the Second World War struggled against criminal prisoners and prisoners who assisted the administration of camps. The forms of resistance were similar but they developed in an organised manner, to various extents, in all camps of the special regime. During 1951–1952, the resistance of political prisoners in the special regime camps manifested itself by single actions and hunger-strikes. While the community of political prisoners was taking shape, these spontaneous unorganised protest actions developed into mass strikes and revolts.In 1953–1954 thousands of prisoners of Gorlag, Rechlag and Steplag camps went on strike. During the general strikes. the strength of the relations among the communities of political prisoners and the effectiveness of methods of unarmed struggle were tested. Although the largest strikes during 1953–1954 in the special regime camps were suppressed, the Soviet government was forced to satisfy the demands of the prisoners: liquidate the special imprisonment regime; create better working and living conditions; begin the review of criminal cases of political prisoners and then to rehabilitate them. By the end of 1956, most political prisoners were released from the camps and amnestied.
Keywords: Soviet occupation; Gulag; political prisoners; resistance